PERANCANGAN SISTEM PENJADWALAN PRODUKSI DENGAN MENGGUNAKAN PROGRAM VISUAL BASIC - Firman Ardiansyah Ekoanindiyo; Antono Adhi; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2011)
Scheduling of production basically resource allocation to finish a group of work to be fulfilling certain criterion. The criterion can in the form of minimum completion of task time, usage of maximal resource, generated total cost minimum and other criterions. There is three important aspect to determine accomplishment of criterion, that is determination of production lot, determination of work sequence and determination of production capacities which is needed. In a industry of manufacture, scheduling needed in operator energy allocation, machine, and equipment of production, process sequence, product type, purchasing of raw material and others. Research of scheduling of production have a purpose to minimize make-span in scheduling of this production can be used constructively program of computer its use Visual Basic software. Keywords: Production Scheduling, Make-span, Visual Basic Software